Lexical Sesquipedaliophobia Across Academic and Sociodemographic Contexts: Basis for Developing a Targeted Intervention Scheme - Caloc, Louie Jay; Baradillo, Danilo (International Journal of Language and Literary Studies, 2026)
Lexical sesquipedaliophobia—the anxiety associated with encountering long and complex words—presents a significant yet underexplored barrier in foreign language learning. This quantitative study employed a non-experimental descriptive-comparative design to examine the level of lexical sesquipedaliophobia among tertiary students in the Davao Region, Philippines, with attention to grouping variables such as degree program, provincial classification, school type, and sex. Data were gathered from a stratified sample of 330 students across five academic programs using the Lexical Sesquipedaliophobia Scale (LSS), a modified instrument adapted from Horwitz et al.’s (1986) FLCAS. Descriptive and inferential statistics revealed consistently high mean ratings on communication apprehension, test anxiety, and fear of negative evaluation. Significant differences in anxiety levels were also found across academic areas, geographic locations, institutional types, and sex. These findings provide an empirical foundation for the design of a targeted intervention scheme titled “LEXI-CALM: Lexical Confidence and Anxiety-Lowering Modules for Academic Lengthy and Complex Word Use.” The study highlights the importance of addressing affective factors in vocabulary instruction and supports the development of context-sensitive, learner-informed interventions that respond to the academic and sociocultural variables shaping lexical anxiety in foreign language classrooms.